ANALISIS SISTEM AKUNTANSI PENGELOLAAN PAJAK HOTEL PADA BADAN PENDAPATAN DAERAH KOTA MANADO - Syaefudin, Fanesa Isalia Minanda; Pongajow, Jacqlin Pongajow; Maramis, Lidya Anggiline; Paendong, Yelly Sjenny; Sumendap, Pricilia Christina; Runtuwene, Treesje Lusje; Wowor, Pingkan Elni (Journal of Information System, Applied, Management, Accounting and Research, 2025)
The city of Manado as a business and tourism center in North Sulawesi has great potential in collecting hotel taxes. Hotel tax is one source of Regional Original Income (PAD). However, there are still several problems with the collection mechanism. So this affects the implementation of hotel tax revenues which is not optimal. This research aims to find out whether the hotel tax management accounting system at the Manado City Regional Revenue Agency is in accordance with Regional Regulation No. 2 of 2011. The research method used is qualitative with a descriptive approach. Data collection techniques through observation, interviews and documentation. The research results show that the hotel tax management system is good, but there are still several weaknesses that affect the effectiveness of tax revenue in Manado City.